Exploring Tourism Facilities to Enhance Ecotourism in Bukit Lawang - Ginting, Nurlisa; Ristika, Firda; Siregar, Narosu (International Journal of Architecture and Urbanism, 2026)
Ecotourism is a form of tourism that promotes travel in natural settings, which is currently favoured by visitors. This rising interest for ecotourism will only be satisfactory if the destination could provide sufficient tourism facilities. Such facilities enable travellers to access the destination as well as allow them to experience the distinctiveness of a place and appreciate the natural environment. Bukit Lawang is one of the most popular ecotourism destinations in Indonesia. Located at the rainforest in Gunung Leuser National Park, Bukit Lawang offers visitors with hiking trails and opportunity to observe orangutans in their native habitat. This paper aims to identify the elements of tourism supporting facilities in Bukit Lawang. By implementing a mixed method research, this paper adapts ecotourism variables and triangulates data from observation, questionnaires, and interviews. It is found that tourism supporting facilities in Bukit Lawang remain unsatisfactory because they are yet to be properly organised. To improve the condition, the facilities and services in Bukit Lawang need to be adequately structured, arranged, and managed by strengthening the body of the Destination Management Organisation (DMO) thus the objective of ecotourism in Bukit Lawang can be achieved.